On the origin of electrodeposition mechanism of ZnO on ITO substrate - Lee, J; Nam, SC; Tak, Y (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2005)
Zinc oxide (ZnO) was potentiostatically deposited on indium tin oxide (ITO) substrates. Comparing of the theoretical mass/charge ratio with experimental value measured by in-situ electrochemical quartz crystal microbalance, the origin of deposition mechanism of ZnO could be explained as follows: (i) surface pH enhancement due to the adsorption of hydroxide ion; (ii) the formation of intermediate species (i.e., zinc hydroxide (Zn(OH)(+)); (iii) ZnO deposition with production of water. Ex-situ morphological and structural analyses by scanning electron microscope and X-ray diffraction strongly supported the deposition mechanism of ZnO. This also showed that hexagonal shaped ZnO islands were first formed on ITO cathode and grew into compact ZnO films, and the formation behaviour of ZnO was clearly explained via analysis of the profile of measured current.
Keywords: ELECTROCHEMICAL DEPOSITION; ZINC-OXIDE; FILMS